2016
DOI: 10.1016/j.chemosphere.2016.08.100
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-desorption of oxytetracycline on marine sediments: Kinetics and influencing factors

Abstract: h i g h l i g h t sOTC sorption on marine sediments were investigated using batch and stirred flow chamber (SFC) experiments. Second order kinetic model successfully described OTC adsorption/desorption kinetics. Adsorption/desorption rate is controlled by diffusive mass transfer process. Solution pH and salinity have large impact on the extent of OTC sorption. A weak hysteresis was observed in OTC adsorption-desorption process. a r t i c l e i n f o b s t r a c tTo reveal the kinetics and mechanisms of antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Additionally, the adsorption of TCs by active sludge could be well explained by Langmuir isotherm model (Li & Zhang, 2016;Mihciokur & Oguz, 2016;Prado et al, 2009a). Li and Zhang (2016) indicated that a pseudo-second-order model could successfully describe adsorption and desorption kinetics of TC and OTC on activated sludge.…”
Section: Removal By Biosorptionmentioning
confidence: 85%
“…Additionally, the adsorption of TCs by active sludge could be well explained by Langmuir isotherm model (Li & Zhang, 2016;Mihciokur & Oguz, 2016;Prado et al, 2009a). Li and Zhang (2016) indicated that a pseudo-second-order model could successfully describe adsorption and desorption kinetics of TC and OTC on activated sludge.…”
Section: Removal By Biosorptionmentioning
confidence: 85%
“…In this case, the cations of CIP enhanced its sorption capacity on the negatively charged sediment particles through electrostatic attraction. The sorption amounts of all the antibiotics on sediment H were slightly (ANOVA; p > 0.05) greater than those on sediment L. This was because sediment with a high organic matter and/or ironaluminum oxides has a stronger sorption capacity for antibiotics (Cao et al 2015;Li and Zhang 2016;Riaz et al 2018).…”
Section: Sorption Kinetics Of Antibioticsmentioning
confidence: 90%
“…The sediment samples were placed into a freeze dryer (Songyuan, China) for 4 days to remove all the water. The detail information of marine sediment samples was described previously (Li and Zhang 2016). Briefly, the point of zero charge (PZC) was 9.2 for sediment BHB, and 9.4 for sediment LZB, suggesting a small amount of net positive charge during adsorption/ desorption experiments (pH = 7.7~8.0); the total organic carbon contents in sediment BHB and LZB were 0.48% and 0.15%, respectively; the clay fraction (< 4 μm) in sediment BHB and LZB were 30.7% and 8.5%, respectively.…”
Section: Chemicals and Marine Sediment Samplesmentioning
confidence: 99%